Authenthic Assessment Instrument in Attitude for Fourth Grade Elementary School Students - Ramadan, Zaka Hadikusuma; Hastuti, Tity (International Journal of Elementary Education, 2021)
Assessment and imprisonment are two things that can not be separated, but currently, teachers still have difficulty in compiling instruments and conduct authentic assessments,  especially in the realm of attitude. It will directly affect the results of learning if not completed. The purpose of the study was to develop an authentic assessment instrument in the realm of attitudes for grade IV elementary students. This type of research is a development with the method used is formative research conducted two stages namely preliminary and formative evaluation stage. the subject of the study was  2  teachers and  20  students. Research instruments use expert evaluation validation sheets, materials, and thematics. Analyze data using descriptive analysis.  Instrumen authentic assessment on the realm of attitude for grade IV students who are attachedn on the theme of "My Hero" in the form of assessment rubrics and assessment formats. The results showed that expert validation results gained an average percentage of  97.50%  in the excellent category. So, the authentic assessment instrument developed deserves to be used to measure students' attitudes in learning.